Trajectories of Neurological Recovery 12 Months after Hospitalization for COVID‐19: A Prospective Longitudinal Study. (20th December 2022) - Frontera, Jennifer
Abstract: Background: Little is known about trajectories of recovery 12‐months after hospitalization for severe COVID. Method: We conducted a prospective, longitudinal cohort study of patients with and without neurological complications during index hospitalization for COVID‐19 from March 10, 2020‐May 20, 2020. Phone follow‐up batteries were performed at 6‐ and 12‐months post‐COVID symptom onset. The primary 12‐month outcome was the modified Rankin Scale (mRS) comparing patients with or without neurological complications using multivariable ordinal analysis. Secondary outcomes included: activities of daily living (Barthel Index), telephone Montreal Cognitive Assessment (t‐MoCA) and Neuro‐QoL batteries for anxiety, depression, fatigue and sleep. Changes in outcome scores from 6 to 12‐months were compared using non‐parametric paired‐samples sign test. Result: Twelve‐month follow‐up was completed in N = 242 patients (median age 65, 64% male, 34% intubated during hospitalization) and N = 174 completed both 6‐ and 12‐month follow‐up. At 12‐months 197/227 (87%) had ≥1 abnormal metric: mRS>0 (75%), Barthel<100 (64%), t‐MoCA≤18 (50%), high anxiety (7%), depression (4%), fatigue (9%) and poor sleep (10%). 12‐month mRS scores did not differ significantly among those with (N = 113) or without (N = 129) neurological complications during hospitalization after adjusting for age, sex, race, pre‐COVID mRS and intubation status (adjusted OR 1.4, 95% CI0.8‐2.5), though those with neurological complications had higher fatigue scores (T‐score 47 vs 44, P = 0.037). Significant improvements in outcome trajectories from 6‐ to 12‐months were observed in t‐MoCA scores (56% improved, median difference 1 point, P = 0.002), and Neuro‐QoL anxiety scores (45% improved, P = 0.003). Non‐significant improvements occurred in fatigue, sleep and depression scores in 48%, 48% and 38% of patients, respectively. Barthel and mRS scores remained unchanged between 6 and 12‐months in >50% of patients. Conclusion: At 12‐months post‐hospitalization for severe COVID, 87% of patients had ongoing abnormalities in functional, cognitive or Neuro‐QoL metrics and abnormal cognition persisted in 50% of patients without a prior history of dementia/cognitive abnormality. Only fatigue severity differed significantly between patients with or without neurological complications during index hospitalization. However, significant improvements in cognitive (t‐MoCA) and anxiety (Neuro‐QoL) scores occurred in 56% and 45% of patients, respectively, between 6‐ to 12‐months. These results may not be generalizable to those with mild/moderate COVID.